2014
DOI: 10.1093/jxb/ert460
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering early events involved in hyperosmotic stress-induced programmed cell death in tobacco BY-2 cells

Abstract: Hyperosmotic stresses represent one of the major constraints that adversely affect plants growth, development, and productivity. In this study, the focus was on early responses to hyperosmotic stress- (NaCl and sorbitol) induced reactive oxygen species (ROS) generation, cytosolic Ca2+ concentration ([Ca2+]cyt) increase, ion fluxes, and mitochondrial potential variations, and on their links in pathways leading to programmed cell death (PCD). By using BY-2 tobacco cells, it was shown that both NaCl- and sorbitol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
37
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 62 publications
7
37
0
Order By: Relevance
“…In response to DON we recorded a time-dependent swelling and depolarization of the mitochondrion clearly indicating mitochondrial dysfunction. This mitochondrial swelling, decrease in m , and the cell death were largely attenuated in the presence of CsA, a blocker of PTP [36,37,57] as already observed in different environmentally and developmentally regulated cell death [5,17]. It is noteworthy that CsA was also efficient in decreasing DON-induced ROS generation (Supplemental Fig.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…In response to DON we recorded a time-dependent swelling and depolarization of the mitochondrion clearly indicating mitochondrial dysfunction. This mitochondrial swelling, decrease in m , and the cell death were largely attenuated in the presence of CsA, a blocker of PTP [36,37,57] as already observed in different environmentally and developmentally regulated cell death [5,17]. It is noteworthy that CsA was also efficient in decreasing DON-induced ROS generation (Supplemental Fig.…”
Section: Discussionsupporting
confidence: 73%
“…Nicotiana tabacum BY2 cell suspensions were grown in Murashige and Skoog medium (MS medium) at pH 5.8 [17]. They were maintained at 22 ± 2 • C in darkness with continuous shaking at 120 rpm.…”
Section: Plant Cell Culture Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental systems to understand the effects of drought have incorporated cell-impermeable high molecular weight polyethylene glycol (PEG;Lagerwerff et al, 1961;Verslues et al, 1998). The use of PEG showed that drought stress response could be separated into components of high osmotic pressure effects and of high salt toxicity effects, with each exhibiting distinct transcriptome profiles (Patade et al, 2012;Monetti et al, 2014). Indeed, PEG-generated osmotic stress was used to select for novel drought-resistant rice genotypes in embryogenic calli.…”
mentioning
confidence: 99%
“…Although involvement of O 2 •À produced via the function of NADPH oxidase is implicated in PCD pathway under salt and osmotic stress, signals activated by ionic salt and nonionic osmotic stress inducer (i.e., sorbitol) did not show extensive overlap (Monetti et al 2014;Petrov et al 2015), indicating the specificity of the mechanism regulating PCD under these stresses. Specific feature of salt-induced PCD is characterized by ion disequilibrium that may be due to invasion of Na + into the cytosol accompanied by a decrease in K + .…”
Section: Programmed Cell Death Regulated By Ros Under Abiotic Stressmentioning
confidence: 93%